Methodological approaches to the organization of packaging production - Gavva, Oleksandr M.; Volodin, Oleksandr; Butyk, Taras (My University, 2024)
The features of the analysis of the optimal organization of packaging production in terms of logistics are considered. Examples of the formation of various technological cycles with the most common types of product placement are given. The methodology for organizing packaging production includes the following main stages: analysis, planning, organization, control. The following methods and techniques have been studied to organize packaging production. Integration of logistics processes, which allows to increase the efficiency of the logistics system and reduce costs. Automation of logistics processes, which increases the speed and accuracy of logistics operations. Use of information technology to improve the efficiency of logistics management. Efficient organization of packaging production to ensure production continuity. Improving the quality of packaging materials and products. Modern trends in the organization of packaging production.

Розглянуто особливості аналізу оптимальної організації пакувального виробництва з точки зору логістики. Наведено приклади формування різних технологічних циклів з найпоширенішими типами розміщення продукції. Методологія організації пакувального виробництва включає такі основні етапи: аналіз, планування, організація, контроль. Досліджено наступні методи та та прийоми організації пакувального виробництва. Інтеграція логістичних процесів, що дозволяє підвищити ефективність логістичної системи та знизити витрати. Автоматизація логістичних процесів, що підвищує швидкість і точність виконання логістичних операцій. Використання інформаційних технологій для підвищення ефективності управління логістикою. Ефективна організація пакувального виробництва для забезпечення безперервності виробництва. Підвищення якості пакувальних матеріалів та продукції. Сучасні тенденції в організації пакувального виробництва.
Keywords: кафедра мехатроніки та пакувальної техніки; кафедра машин і апаратів харчових та фармацевтичних виробництв; methodology; pacaging production; logistics processes; system efficiency; accuracy of execution; методологія; пакувальне виробництво; логістичні процеси; ефективність системи; точність виконання